Efektivitas Model Direct Instruction Terhadap Kemampuan Menulis Puisi Siswa Kelas X Sman 5 Lubuklinggau - Cekman Cekman*; Jamaludin Jamaludin (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
The purpose of this study was to determine the effectiveness of direct instruction learning model toward the students’ ability in writing poetry in class X of SMAN 5 Lubuklinggau and to determine students' responses toward the ability of writing poetry. The research method in this study used a quasi-experimental method. Data collection techniques used was tests and questionnaires. Data analysis techniques for test results used determining the average score and standard deviation, normality test, and t- test. The results of the t-test calculation was obtained the t-count is 6.24 when compared to t-table at a significance level of 5%, namely: 6.24 2.05. The results of the research showed that the direct instruction learning model was effective toward the ability in writing poetry.